Visionary pricing reflections and advances in honor of Dan Nimer - Smith, Gerald E.; Nimer, Dan (Advances in business marketing & purchasing ;, 2012)
Visionary Pricing is dedicated to Dan Nimer, pioneer of pricing and price management. The volume features leading edge thinking from today's preeminent pricing thought leaders from North America, Europe, and Asia who originally came together 30 years ago to encourage the development of pricing. They now assess the present and future destiny of pricing, pricing innovation, and pricing paradigms that are influencing the evolution of pricing throughout the world. The volume contains four sections: Section 1 interviews Nimer and presents his views on the emergence of value-based pricing as an influential pricing paradigm of the 21st century. Section 2 focuses on pricing strategy and competitive advantage.Section 3 focuses on the defining role of value in pricing. Section 4 focuses on pricing capability and innovation.